Higher bat and prey abundance at organic than conventional soybean fields. (October 2018) - Put, Julia E.; Mitchell, Greg W.; Fahrig, Lenore
Abstract: Studies that have compared biodiversity at organic and conventional farms have generally found that there are more species in greater abundances at organic farms. One widespread problem with previous studies is that most do not control for differences in field structure and landscape composition at organic and conventional farms. Thus, the effects observed may be due to factors other than organic farming practices. We addressed this problem by selecting matched organic-conventional pairs of soybean fields such that in each pair the soybean fields were similar in size, hedgerow length, and surrounding landscape composition within 1 km, 2 km and 3 km of the fields. At each of our 16 field pairs (32 sites), we measured relative differences in bat species richness and abundance using acoustic bat recorders, and bat prey availability using black-light traps. We predicted that organic soybean fields would have greater bat species richness, bat abundance and bat prey abundance than conventional soybean fields due to the prohibition of synthetic pesticides and longer more diverse crop rotations in organic fields, both of which should benefit bat insect prey. We found that organic soybean fields had higher bat species richness, bat abundance and bat prey abundance than conventional fields, after controlling for the effect of differences in soybean height between conventional and organic fields. Our results suggest that the management practices used at organic farms benefit bats at least in part by providing greater bat prey availability. Highlights: Bat richness and abundance greater at organic than conventional fields. Prey abundance also greater at organic than conventional fields. However, bats do not appear to be responding to prey abundance alone. An increase in the extent of organic agriculture would benefit bats.